(untitled) (Research, Society and Development, 2021)
The genus Psidium belongs to the Myrtaceae family and comprises important botanical species, especially the guava tree (Psidium guajava L.). The essential oil (EO) of this species has already conducted several scientific studies due to its chemical composition and pharmacological properties, highlighting its antifungal action and antimicrobial activities. In this work, two varieties of Psidium, Psidium guajava var. pomifera (Paluma) and Psidium guajava var. pyrifera (Kumagai), were collected in different locations in the municipality of Itacoatiara - AM, the OE of the leaves were evaluated for chemical composition and antimicrobial activity. The extraction of essential oil was performed by hydrodistillation in a Clevenger-type apparatus for 4 hours, quantitative and qualitative analyzes were performed by gas chromatography coupled with mass spectrometry. The antimicrobial activities were evaluated using the in vitro test on the inhibition of bacterial growth of Escherichia coli (Migula 1895) Castellani and Chalmers 1919, Salmonella sp and Staphylococcus aureus Rosenbach 1884 and mycelial growth of the phytopathogens Candida albicans (CP Robin) Berkhout 1923 and Candida parapsilosis (Ashford) Langeron & Talice 1932. The chemical composition revealed the presence of the monoterpenes: D_limonene, α-pinene, 1.8 - cineol, and the sequiterpenes: trans-nerolidol, trans-caryophyllene, caryophyllene oxide and α-humulene as constituents majority in the evaluated samples. Regarding the biological tests performed, it was possible to observe antimicrobial activity in all strains studied. Based on the results, it is concluded that essential oils of these varieties of P. guajava have promising activities and can be considered as a new source of antimicrobial bioactive compounds.